2010
DOI: 10.1210/jc.2009-2528
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Biokinetics and Radioiodine Exposure after Recombinant Human Thyrotropin-Assisted Remnant Ablation in Comparison with Thyroid Hormone Withdrawal

Abstract: In comparison with thyroid hormone withdrawal, rhTSH is associated with longer remnant half-life of radioactive iodine while also reducing radiation exposure to the rest of the body and also to the general public who come in contact with such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 25 publications
8
36
0
1
Order By: Relevance
“…3 Means and standard deviations of other chemistry profiles (ALP, total bilirubin, and triglyceride) for the group receiving traditional thyroid hormone withdrawal (THW) and the group receiving recombinant human thyroidstimulating hormone (rh-TSH). There were no statistically significant differences between the two groups the body [18], not only patients with metabolic syndrome, but also elderly patients and those with large thyroid remnants can more safely undergo rh-TSH than THW.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…3 Means and standard deviations of other chemistry profiles (ALP, total bilirubin, and triglyceride) for the group receiving traditional thyroid hormone withdrawal (THW) and the group receiving recombinant human thyroidstimulating hormone (rh-TSH). There were no statistically significant differences between the two groups the body [18], not only patients with metabolic syndrome, but also elderly patients and those with large thyroid remnants can more safely undergo rh-TSH than THW.…”
Section: Discussionmentioning
confidence: 76%
“…Another study on iodine biokinetics showed the effective half-life in the remnant thyroid tissue was significantly longer after rh-TSH than THW, reducing radiation exposure to the rest of the body and to the general public who come in contact with such patients [18]. In these patients, the efficacy of radioiodine treatment is related to the radiation dose delivered to remnant and neoplastic thyroid tissue [19].…”
Section: Discussionmentioning
confidence: 99%
“…Three trials reported the effects on the blood and bone marrow [10,16,17]. But the study parameters were not identical in these trials.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, preparation for radioiodine treatment with rhTSH instead of THW has been proposed to induce less bone marrow toxicity. rhTSH preparation is associated with a lower red marrow absorbed dose [31], and in a study performed in 15 elderly DTC patients no clinically relevant bone marrow toxicity was observed after radioiodine therapy [32]. However, no differences in peripheral blood counts were found between patients prepared with THW and rhTSH in a larger-scale study [33].…”
Section: Radioiodine Therapymentioning
confidence: 99%